(untitled) (Nigerian Journal of Physiological Sciences, 2025)
One of the factors characterizing suboptimal breastfeeding is insufficient human milk production. In most African settings, special food items are regularly used to promote human milk production. These food items, called galactagogues, are used in Nigeria, but their use is undocumented and their amount of intake among lactating mothers is unknown. This study aimed to document the galactagogue consumption habits and describe the food items used by some lactating mothers in Nigeria. A cross-sectional study was conducted among 112 mothers who breastfed exclusively in Lagos Nigeria. A pretested, self-reported administered questionnaire was used. All data were coded in a computer program file (STATA, statistical software, version 15.0). The most reported galactagogue was pap (80.8%). Others were tea (46.0%), milk (19.1%), and amala (9.5%). Information concerning galactagogues was mainly from the participants’ mothers (35.9%), while media/ internet had little influence (4.2%). Galactagogues are common in Nigeria, and they signify an important part of the nutrition of lactating mothers. These results could contribute to the knowledge of breastfeeding activities in Nigeria and encourage further research to produce robust facts about galactagogues’ safety and scientific efficacy to support evidence-based approaches and advance breastfeeding concerns.